KEPITING BAKAU DI KAWASAN MANGROVE PERING KABUPATEN NATUNA KEPULAUAN RIAU - Ikha Safitri; Mega Sari Juane Sofiana (Jurnal Perikanan Unram, 2024)
Mangrove area of Pering located in East Bunguran District which has the potential for a mangrove ecosystem. This area has an important ecological role as a habitat for various types of aquatic biota, one of them is mud crabs (Scylla sp.). This biota is widely distributed in Indonesian coast, including mangrove area of Pering. Scylla sp. as a key species that responsible for various processes in mangrove areas. The abundance of mud crabs is still under threat from nature and human activities, such as overfishing and overexploitation. Therefore, the aim of this research was to identify the types of mud crabs species from the mangrove area of Pering, Natuna Regency. The research was conducted in August 2023, the sample collection was done using the exploration method. Thus, the identification was carried out based on the morphological characteristics. The type of mud crabs found in the mangrove area of Pering, Natuna Regency, Riau Islands consisted of two species, such as Scylla serrata and Scylla tranquebarica.